1982
DOI: 10.1084/jem.155.4.1037
|View full text |Cite
|
Sign up to set email alerts
|

T cells cooperating in the induction of delayed-type hypersensitivity act via the linked recognition of antigenic determinants.

Abstract: A requirement for specific cellular collaboration has been demonstrated for the induction of humoral antibody (1-3), cytotoxic T cells (4,5), and for those helper T cells able to help the induction of B cells (6). Leung and Ada (7) have recently shown that antigen-specific cells can significantly enhance the primary in vitro induction of delayed-type hypersensitivity (DTH)a to influenza virus. We independently developed an in vitro system in which the induction of significant DTH reactivity is dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…The second is that this was accomplished by enlisting the response of tumor (self)-specific CD4 T cells through the help provided by CD4 T cells specific for a nonself-determinant. This mechanism is consistent with predictions based on associative recognition of linked T cell determinants (29) and validates the basic tenet of the two-signal model for T cell activation (9,30). We had previously demonstrated that the simultaneous injection of plasmids coding for -VTSA-and -NVDP-in different sites of the same organ did not generate immunity to MUC.1 (8), ruling out that -NVDP-may serve merely as adjuvant.…”
Section: Discussionsupporting
confidence: 65%
“…The second is that this was accomplished by enlisting the response of tumor (self)-specific CD4 T cells through the help provided by CD4 T cells specific for a nonself-determinant. This mechanism is consistent with predictions based on associative recognition of linked T cell determinants (29) and validates the basic tenet of the two-signal model for T cell activation (9,30). We had previously demonstrated that the simultaneous injection of plasmids coding for -VTSA-and -NVDP-in different sites of the same organ did not generate immunity to MUC.1 (8), ruling out that -NVDP-may serve merely as adjuvant.…”
Section: Discussionsupporting
confidence: 65%
“…Through the use of peptide antigens and other experimental systems, investigators have previously demonstrated that priming of an active CD8 ϩ T-cell response in vivo requires covalent linkage between the MHC class II epitope that binds the CD4 ϩ T-cell receptor (TCR) and the MHC class I epitope that attracts the cognate CD8 ϩ effector cell; the implication being that such epitopes must be present in the same APC for the induction of a productive immune response. [46][47][48][49] Clearly, however, other mechanisms governing specificity must regulate CD8 responses, otherwise almost any soluble antigen might provide help for CD8 ϩ T cells recognizing almost any presented MHC class I peptide. Our observations detail a mechanism by which such specificity might be imparted.…”
Section: Discussionmentioning
confidence: 99%
“…We start from the premise, for which we believe there is much indirect and direct evidence, that the activation of CD4+ pTh cells in general requires CD4+/CD4+ T cell interactions mediated by the recognition of linked antigenic epitopes. These interactions between specific T cells are envisaged to be mediated by the recognition of antigens presented by antigen presenting cells (APCs), such as B cells or macrophages, by the interacting CD4+ T cells [35,36]. A valid description of the decision criterion must account for the conditions of immunisation known to determine whether Th1 or Th2 cells are generated.…”
Section: The Cellular Basis Of Immune Deviation and The Definition Ofmentioning
confidence: 99%